INFLUÊNCIA DA TÉCNICA DE FOTOPOLIMERIZAÇÃO NO GRAU DE CONVERSÃO DE UM CIMENTO RESINOSO E NA RETENÇÃO DE PINOS DE FIBRA DE VIDRO À DENTINA RADICULAR - Boing, Thaynara Faelly (2015)
The purpose of this study was to evaluate the influence of two polymerization techniques on conversion degree (DC) of the resin cements and on retention of glass fiber posts in the different thirds of root dentine. For this purpose, it was selected twenty extracted mandibular premolars, which were sectioned after the cementumenamel junction, and the roots were treated endodontically. After a week, the posts spaces were prepared and the roots were randomly divided into two groups (n=10),according to the mode of polymerization of the dual resin cement (RelyX™ U200 – 3M ESPE): GFC - activation mode Continuous and GFS - activation mode Soft start (Ramp). The intraradicular posts (White Post DC - FGM) were cemented according to the manufacturer's recommendations. After storage in distilled water at 37 ° C for one week, the roots were cross-sectioned in six discs of 1 mm thickness each, and the thirds coronary (TC), medium (TM) and apical (TA) of the root canal were identified.To assess the degree DC the specimens were submitted to Micro-Raman spectroscopy, and the bond strength by the push-out test at a cross-head speed of 0.5 mm/min. The data were be statistically analyzed by two-way ANOVA and Tukey’s test for contrast of means (α = 0.05). The average values of degree of conversion and standard deviation (SD ) for each group were: GFC : 75.66 ± 5.51 , GFS : 77.38 ± 5.66, compared to thirds GFC : TC : 73.87 ± 5.50, TM : 74.59 ± 4.86 and TA : 78.50 ± 5.57 , GFS : TC : 77.79 ± 6.16 , TM : 77.14 ± 5.77 and TA : 77.21 ± 5.79 . There was no significant difference between the techniques of photoactivation or between root thirds. For bond strength ( MPa ) mean (SD) values and standard deviation were : GFC : 18.46 ± 6.23 , GFS : 22.88 ± 5.76 , compared to thirds , GFC : TC : 14.32 ± 3.40 , TM : 15.75 ± 3.20 , TA : 25.30 ± 4.89 , GFS : TC : 19.83 ± 3.97 , TM : 22.21 ±5.59 , MT : 26 , 59 ± 5.79 . The activation mode GFS was statistically higher than the 11 GFC (p = 0.036). And the apical obtained resistance values statistically superior compared to other union -thirds (p < 0.001). It can be concluded that the bond strength was significantly affected by the technique of photoactivation and the root region, and that the degree of conversion was not affected either by photoactivation technique nor the root region.